Secondary School Teachers' and Students' Perspectives on Cooperative Group Work Assessment Challenges in Ethiopia - Abate Demissie Gedamu; Getu Lema Shewangezaw (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2020)
Cooperative Learning (CL) has been encouraged in Ethiopia's secondary schools as an important strategy to facilitate effective student learning. However, the effectiveness of CL hinges, among other factors, on appropriate assessment of students' group work. Challenges faced by teachers and students in implementing assessment of group work have remained an obstacle to the effective use of CL. The aim of this study was therefore to examine what Ethiopian secondary school teachers and students, respectively, consider to be problems and obstacles in the way of efficiently implementing student the cooperative group work assessment. Accordingly, 213 teachers and 212 students were randomly selected for a questionnaire survey. In addition, two teachers and five students were also interviewed and a focus group discussion (FGD) was carried out in each of the five schools selected for data gathering. The data acquired through the questionnaire was analyzed through one-sample t-test while the data obtained through interviews and FGD were analyzed through qualitative verbal descriptions. The findings indicate the main challenges from the point of view of the teachers to be their inadequate training on the assessment of group work process and individual contributions; uncertainty on what should be assessed, and heavy workloads. From the students' perspective, the main challenges were inadequate teacher support and follow up and equal reward for unequal contribution by members to group work.